Assessment of the accumulation of some trace metals in whole body of fresh water shrimp Atyaephyra desmaresti mesopotamica from Shatt Al-Arab River, Basrah, Iraq - Al-Yaseri, S.T.L. (Mesopotamian Journal of Marine Sciences, 2022)
Concentrations of heavy metals (Pb, Mn, Ni, Fe, Cu, and Zn) were determined in shrimp Atyaephyra desmaresti mesopotamica collected from Shatt Al-Arab River, Basrah, Iraq. The elements content were determined in whole body biomass. The seasonal variations of the element concentrations, and the relationship between element concentrations in males and females were estimated in this study. Measurements were done to evaluate trace metals in shrimps tissues in Qurmat-Ali in Shatt Al-Arab River between summer (May- August) 2008 and spring (March and April) 2009. Samples were collected seasonally. Tissue samples were analyzed by flame atomic absorption spectrophotometry. Females accumulated the trace metals in their bodies in spring higher than other seasons. Males accumulated the trace metals in their bodies in Spring higher than other seasons, except for Pb and Mn. Regarding to concentrations; the highest values were 141.80 µg g-1 d.w in males and 136.79 µg g-1 d.w in females for Iron, while the lowest values were 2.49 µg g-1 d.w in males and 2.96 µg g-1 d.w in females for Lead. Regarding to seasons; in Summer the concentrations of trace metals were higher in males than in females, except Zn, in Autumn they were higher in males than in females, except Pb and Ni, in Winter they were higher in males than in females, except Pb and Zn, in Spring they were higher in males than in females, except Pb, Mn and Zn.